High-Accuracy Range Detection Radar Sensor for Hydraulic Cylinders - Ayhan, Serdal; Scherr, Steffen; Pahl, Philipp; Kayser, Thorsten; Pauli, Mario; Zwick, Thomas (IEEE sensors journal, 2014)
Industrial automation requires highly precise distance measurement sensors. Accurate detection of the piston position is indispensable for the control and monitoring of hydraulic cylinder applications. Known external and integrated solutions are subject to many limitations as for example in accuracy, in measurement length, or in price. A promising approach consists in the use of precise and low-cost radar sensors. The developed K-band frequency modulated continuous wave (FMCW) radar system in this paper detects the piston position in a hydraulic cylinder based on the guided propagation of a radar signal. The dielectric characteristics of the hydraulic oil are obtained for this purpose by permittivity measurement methods. Influences of the hydraulic oil on wave propagation in cylindrical waveguides as well as mechanical requirements associated with this new approach are investigated. The design of an adapted oil- and pressure-resistant transition between the radar sensor and the hydraulic cylinder and a novel calibration method will be described and verified under real measurement conditions. At a measurement repetition rate of 2 kHz, an accuracy of well below 200 μm was achieved for a hydraulic cylinder of 1 m in length.